IMPLEMENTATION OF POLICY EDUCATION CURRICULUM ENGLISH COURSE ELEMENTARY LEVEL (CASE STUDY AT PUSDIKBANMIN KODIKLATAL LANGUAGE SCHOOL) - Asis Asis; Mas Roro Lilik; Nuhman Nuhman (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2021)
Education has an important role in the progress of a nation to improve the quality of human resources. This is because education still has a significant influence and is the main institution in the preparation of quality human resources, including education in the Navy. The success of educational attainment in the Navy refers to the education component and one of these important components is the curriculum. The curriculum is the main factor in realizing the goals and objectives of education. The development of the Navy's education curriculum is directed at achieving the efficiency and effectiveness of providing tiered and continuous education in order to anticipate the development of science and technology as well as the demands for the implementation of the tasks at hand. This study aims to determine the extent to which the implementation of the curriculum policy for the Elementary Level Intensive English Course (KIBI) for the Indonesian Navy based on Kasal Decree Number Kep/699/VI/2007 at Sebasa Pusdikbanmin. The method used in this study is a qualitative descriptive method with Van Metter and Van Horn frameworks as parameters to determine the inhibiting and supporting factors in the Implementation of the Education Curriculum Policy for the Indonesian Navy Elementary Level English Course at the Language School Pusdikbanmin Kodiklatal. In the results, there are several recommended alternatives, namely increasing the capacity of existing human resources (educational staff, education staff, and students), fulfilling Alins/Alongins and educational facilities, curriculum revision, opening the Advanced Level KIBI program as a standard for mastering English towards the world. navy class and improvement of the administrative system so that it can be used to improve similar educational programs in the coming academic year. Keywords: Education, Curriculum, and Policy.